Automated Labelling Methods For The Extraction Of Liver Region From Magnetic Resonance Images Of Abdomen - Lo, Pechin Chien Pau (2005)
The objective of this thesis is to develop a scheme for detecting the region of interest (ROI), namely, liver from the abdomen MR images, which will pave the way in future for the development of an automated diagnostic and analysis system for liver related diseases. Though a large amount of modalities are available in MR imaging, only T2 images are used for the work carried out in this thesis. A general purpose manual labelling tool for defining ROI and two automated schemes for ROI detection of the liver are presented in this thesis.